Analysis And Design of Decision Support System in Major Assignment at Buddhi High School Using AHP and SAW Methods - Devita Amalia Pertiwi; Benny Daniawan; Yuki Gunawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
Education is one of the important factors to fulfill the needs because education can develop various potential in a person. High school is a process of student development. The selection of major in Buddhi High School still takes a long time and the result are less accurate because of human error factors, and other factors that influence students such as parents’ wishes or follow them, friends. To solve those problems a Decision Support System using the AHP and SAW methods is needed. The AHP and SAW Method require the decision-maker to determine the weight for each attribute. The rating of each attribute must have passed the normalization process of the previous matrix. The result from this system will help students to decide major that suitable with their interest and talents, and also help the school to decide major that suitable according to the appropriate criteria. Calculation with the AHP method has a consistency of 93.96%.